Work after globalization building occupational citizenship - Standing, Guy 1948- (Elgar, 2009)
Refers to Karl Polanyi's "The great transformation" on the rise of industrial citizenship, which hinged on fictitious labour decommodification, superseded by changes in class structure and emergence of a global 'precariat', inequalities, and insecurities. Argues against paternalistic policy responses in favour of an egalitarian strategy to build occupational citizenship, that should be founded on full freedom and basic income security. Considers the phasing out of labour law and a re-orientation of collective bargaining towards 'collaborative bargaining'.